2013
DOI: 10.1016/j.physletb.2012.12.060
|View full text |Cite
|
Sign up to set email alerts
|

Role of T=0 pairing in Gamow–Teller states in N=Z nuclei

Abstract: Gamow-Teller (GT) states in N=Z nuclei with the mass number A from 48 to 64 are studied by using Hartree-Fock-Bogoliubov + quasi-particle random phase approximation (HFB+QRPA) with Skyrme interactions. The isoscalar spin-triplet (T=0,S=1) pairing interaction is taken into account in QRPA calculations. It is found in the context of SU(4) symmetry in the spin-isospin space that the GT strength of lower energy excitations is largely enhanced by the T=0 pairing interaction which works cooperatively with the T=1 pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 37 publications
2
38
0
Order By: Relevance
“…Moreover, the important ingredient of nuclear force -the tensor force was found to play a crucial role in describing the nuclear charge-exchange excitations and β-decay half-lives within the QRPA approaches [40][41][42][43], which inspires much interest to explore the nature of nuclear tensor force [44,45].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the important ingredient of nuclear force -the tensor force was found to play a crucial role in describing the nuclear charge-exchange excitations and β-decay half-lives within the QRPA approaches [40][41][42][43], which inspires much interest to explore the nature of nuclear tensor force [44,45].…”
Section: Introductionmentioning
confidence: 99%
“…[32], a two-peaked structure was observed in the N = Z nucleus 56 Ni and this can provide some insightful information on the isoscalar pairing. Then, the GT transitions in 56 Ni together with other N = Z nuclei were studied by employing the HFB + QRPA theory [33], and this study has highlighted the formation of low-energy GT states in several f -shell nuclei, induced by the isovector and isoscalar pairing interactions and having reasonably strong strength. Recently, it was reported that strong GT states are experimentally observed, only slightly higher than the IAR, in some N = Z + 2 nuclei with mass number A = 42-54 [34].…”
Section: Introductionmentioning
confidence: 99%
“…Fine structures are also reported in pf -shell nuclei 50 Mn, 54 Co, and 58 Cu (T z = 0) [35][36][37][38], 47 V (T z = +1/2) [39], 48 V and 60 Cu (T z = +1) [5,40], 62 Cu (T z = +2) [5], and 64 Cu (T z = +3) [5,41]. However, the GTR structure was not found in 42 Sc (T z = 0) [26] and was not clear in 46 V (T z = 0) [38,42] as well as 44 Sc (T z = +1) [43]. Note that the observed features of the strength distributions and the fragmented GTR structures are distinctively different in these sd-and pf -shell nuclei, showing a marked individuality of their structures (see the discussion in Refs.…”
Section: Almentioning
confidence: 97%
“…[44]). Owing to the repulsive nature, it is expected that the GT strength is mainly pushed up to the higher-E x region and forms the GTR structure (see, e.g., Refs.…”
Section: Overview Of the Gamow-teller Strength Distributionmentioning
confidence: 99%
See 1 more Smart Citation